THE COHESIVE DEVICES IN MONOLOG DISCUSSION TEXTS (English Education Journal, 2012)
Studi ini bertujuan untuk menemukan a) tipe grammatical dan kohesif device, b) bagaimana grammatical dan lexical kohesif device mendukung progress thematic, dan c)bagaimana kohesif device dan progresi thematic mengembangkan cohesi dari diskusi monolog dari mahasiswa 3 kelas speaking universitas Tidar Magelang. Penelitian ini adalah deskriptif kualitatif. Subjek terdiri dari 20 siswa tahun kedua universitas Tidar Magelang. Data didapat dengan spoken tes. Klausa dianalisa menggunakan teori Hasan dan halliday (1976), tema dan rima oleh Gerot dan Wignell (1994) dan paten progresi tematik Paltridge (2000). Hasil menunjukan bahwa tipe kohesif device adalah referensi (34.97%), konjungsi (13.48%), substitusi (1.06%), ellipsis (2.22%), dan lexical (48.27%). Kedua, tipe dari tema yang ditemukan adalah unmarked (42.51%), marked topical (4.63%), tekstual (49.32%), dan tema interpersonal (2.31%). Karena paten yang ditemukan adalah constant/re-iteration (28.47%), zig zag (24.8%0 dan multiple theme pattern (13.08%).This study is meant to find out a) the type of grammatical and lexical cohesive devices, b) how grammatical and lexical cohesive devices support thematic progression, and c) how cohesive devices and thematic progression develop cohesion of monolog discussion texts produced by the students of Speaking 3 class of English Department of Magelang Tidar University. This is a descriptive qualitative study. The subject consisted of 20 students in the second year of English Department of Tidar Magelang University. The spoken test was used to collect the data. The data were monologue-like data and chunked in clauses. The clauses are then analyzed to find the cohesive devices based on Halliday and Hasan (1976), theme-rheme based on Gerot and Wignell (1994), and thematic progression pattern based on Paltridge (2000). After that, the cohesive devices and theme-rheme are analyzed in the way they give connective contribution to thematic progression of discussion text to create cohesion. The findings showed that the types of cohesive devices are reference (34.97%), conjunction (13.48%), substitution (1.06%), ellipsis (2.22%) and lexical (48.27%). Second, the types of theme found are unmarked (42.51%) and marked topical (4.63%), textual (49.32%) and interpersonal theme (2.31%). Because it is spoken language, there is 1.23% Minor Clause. Third, the thematic progression patterns found are constant/ re-iteration (28.47%), zig-zag (24.80%) and multiple theme patterns (13.08%).